The Churches as Ethnoreligious Agents: Interchurch Marriage and Childrearing in Ireland - Rafaoui, Hannah Layla (Trinity College Dublin. School of Religion. Irish School of Ecumenics, 2025)
Ireland has long been a focal point for ethnoreligious conflict, with tensions between competing Protestant and Catholic identities shaping the nation's social fabric. Religious denominations, while contributing to sectarian divides, have also played key roles in peacebuilding efforts, particularly within the context of interchurch marriages. This thesis explores the complex and often contradictory stance of the Irish churches toward mixed marriages, examining how church policies have both reinforced rigid ethnic and religious identities and supported efforts toward reconciliation and ecumenism. By investigating the historical, sociopolitical, and demographic factors influencing interchurch unions, this research highlights the ambiguity inherent in church doctrines and practices related to these marriages. Through a multidisciplinary approach, this study traces the evolution of ethnoreligious identity politics in Ireland, focusing on the role of the Catholic and Protestant churches in shaping communal divisions. While mixed marriages have been historically stigmatized, recent shifts in church attitudes reflect a growing openness to cross-community unions, signaling potential pathways for dismantling the rigid identity constructs that continue to fuel division. This research draws on Irish politics, history, social policy, social psychology, state law, and church law to offer a comprehensive analysis of the challenges faced by interchurch couples and families, exploring the potential for these relationships to bridge longstanding divides in Irish society.
APPROVED
Keywords: Sectarianism; Northern Ireland; Irish Politics; Irish Law; Census; Mixed Marriage; Religion and Identity; Religious Conflict; McCann Case; Ne Temere; Matrimonia Mixta; Intermarriage; Peace; Conflict; Ethnoreligion; Ethnoreligiousity; Catholic Church; Protestant; Anglican Church; Irish Anglicanism; Presbyterians; Interchurch Marriage; Cultural Divide; Social Control; Nationalism; Irish History; Canon Law; Vatican II; Cross-cultural marriage; Ethnic identity; Historical surveys; Social attitudes; Good Friday Agreement; Irish Society; Religious Identity; Social integration; Segregation; Community relations; Christian marriage; Church doctrine; Religious tolerance; Conflict Resolution; Cultural Exchange; Irish Education; Religious policy; Belfast Agreement; Irish Surveys; Historical interactions; Religious pluralism; Identity formation